THU0754-HPR Work status in women with fibromyalgia – a 12-year follow up study. (15th June 2017) - Johannesson, S; Nordeman, L; Joelsson, M; Mannerkorpi, K; Bergenheim, A
Abstract : Background: Fibromyalgia (FM) affects approximately 1–3% of the general population in the Western world and about 10% have been found to report Chronic Widespread Pain (CWP). The work ability is often affected in persons with FM and CWP. Previous research has shown a small improvement of symptoms over time in patient with FM and CWP. Sustain in work has been shown to predict improvement in pain, pressure tenderness, fatigue, stiffness, depression, disturbed sleep, disease specific health, physical aspects and quality of life in persons with FM/CWP. There is lack of research about long-term follow-up of work status in FM and CWP. To enable patients with FM or CWP to sustain in work or return to work it is crucial to gain knowledge about which factors that can affect their work status in the long-term. Objectives: To investigate change in work status and possible predictors of work status after 12 years in a cohort of women with FM and CWP. Methods: In 2004, 166 women with FM and CWP participated in a randomized controlled trial in Sweden investigating effects of patient education and pool exercise. The 166 women were invited to participate in a follow-up study in 2016 in which long-term effects on work status, aspects of health and physical function were investigated. 126 participated in the follow-up study of which 98 were <65 years of age (age of retirement in Sweden) and included in the present study of work status. Data was collected by a standardized interview, a battery of questionnaires and an examination including tests of physical function. Work status refers to percentage of full-time work divided into four categories; 0%/1–49%/50–79%/80–100%. Wilcoxon's signed-rank test was used for comparisons of work status over time within the group. Multivariable forward stepwise logistic regression was used for analyses of predictors of work status after 12 years. The dependent variable was work status dichotomized into <50%/≥50% work. Independent variables were baseline values of age, work status, symptoms of stress, pain intensity, overall health status, leisure time physical activity, walking capacity, health related quality of life and depression. Results: The 98 women showed a significant increase in work status (p<0.001) at the 12 years follow-up. Proportions of work status in category 1–4 at baseline were 56%/10%/22%/10% and at follow-up it was 36%/11%/23%/28%. The participants' age, overall health assessed with Fibromyalgia Impact Questionnaire (FIQ) and health related quality of life assessed with SF-36 Physical component summary (PCS) at baseline predicted work status 10–12 years later. Age (years): OR 0.90 (95% CI 0.84–0.97), p=0.004. FIQ total score (0–100): OR 0.94 (95% CI 0.91–0.97), p<0.001. SF-36 PCS (0–100): OR 1.1 (95% CI 1.0–1.2), p=0.019. Conclusions: Women with FM or CWP appear to improve their work status on group-level over time. Lower age, better overall health and higher health related quality of life at baseline were found to predict higher probability of working 50–100% after 12 years. Disclosure of Interest: None declared